Permberdayaan Masyarakat Menuju Kelurahan Sukahaji yang Mandiri, Berkelanjutan, dan Berkemajuan: Pengabdian - Andika Muchamad Januar; Bilal Arfiansyah; Fathan Naufal Gunawan; Lutviani; Nabila Aulia Putri; Nadyra Riak Pasifica; Rahila Anggani; Shalbi Naila Makarim Nurhidayat; Shelpie; Zaki Faisal Hawari; Mukhlishah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Community Service Program (KKN) is a form of student service to the community that is implemented as part of the Four Pillars of Muhammadiyah and Aisyiah Universities. This activity aims to empower the community, especially in the fields of education, health, environment, and social issues by utilizing the knowledge gained during the lecture period. This community service focuses on the role of KKN students in improving knowledge and understanding of the quality of education in Sukahaji Village, Babakan Ciparay District, Bandung City. Sukahaji Village is one of the areas facing various challenges in providing quality education, supportive health, and a safe and comfortable social environment, especially in terms of adequate access and facilities. Through the KKN program, students strive to contribute by conducting activities such as tutoring, counseling, and providing education to students and the community. The results of the Community Service Program show that the role of KKN students has significantly increased student motivation to learn and broadened the community's understanding of the importance of education, health, the environment, and social issues.